Mechanical thrombectomy as first-line treatment for venous sinus thrombosis: technical considerations and preliminary results using the AngioJet device. (5th December 2011) - Dashti, Shervin R; Hu, Yin C; Yao, Tom; Fiorella, David; Mitha, Alim P; Albuquerque, Felipe C; McDougall, Cameron G
Abstract : Background: Cerebral venous sinus thrombosis (CVT) is an uncommon cause of stroke that is usually treated medically with intravenous heparin therapy followed by long-term anticoagulation therapy. A series of patients with CVT who underwent rheolytic thrombectomy with the AngioJet as a first-line adjunctive treatment in addition to standard anticoagulation therapy is presented. Methods: Prospectively maintained endovascular databases at two institutions were retrospectively reviewed. The available clinical and imaging data were compiled at each institution and combined for analysis. Results: Over 18 months, 13 patients (seven women and six men; age range 17–73 years, median age 45 years) with CVT were treated with rheolytic thrombectomy. Immediate (partial or complete) recanalization of the thrombosed intracranial sinuses was achieved in all patients. At a median radiographic follow-up of 7 months there was continued patency of all recanalized sinuses. Clinical follow-up was available on nine patients: modified Rankin score of 0 in four patients, 1 in three patients and 6 in two patients. Conclusion: This series demonstrates the feasibility of performing mechanical thrombectomy as a first-line treatment for acute CVT. This technique facilitates the prompt restoration of intracranial venous outflow, which may result in rapid neurological and symptomatic improvement.